IMPLEMENTATION FOR SEVENTH-ORDER LOW-PASS CAUER FILTER EMPLOYING SECOND-GENERATION CURRENT-CONTROLLED CONVEYOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
After utilizing adjoint network theory, Bruton transform, frequency-dependent negative resistance (FDNR), component replacement method, and frequency and impedance scaling, a seventh-order low-pass Cauer filter from the normalized RLC prototype circuit is converted to the current-mode filter with fc = 15 kHz, fs = 18.78 kHz, Amax = 0.28 dB, and Amin = 60 dB, which includes only six second-generation current-controlled conveyors (CCCⅡs) and grounded capacitors, does not need any matched conditions, and adjusting bias currents of the CCCⅡs can control performances of the filter, The computer simulation has verified the correctness of this design.
Keywords: Seventh-order low-pass filter; Cauer filter; Current-mode circuits; Second-generation current-controlled conveyors